Revitalizing health service with e-pharmacy: Technology integration in pharmacy service - Dwi Asa Verano; Muhamad Risal Tawil; Kraugusteeliana; Tanti Widia Nurdiani; Diki Prayugo Wibowo (Jurnal Mantik, 2023)
To improve the quality and accessibility of services, health services must maintain pace with technological advancements. One of the technologies that can be implemented in pharmacy services is an e-pharmacy-integrated medication sales information system. This can accelerate drug data processing, inventory management, and drug sales transactions, as well as make it easier for users to obtain accurate and up-to-date drug information. The integration of technology in pharmacy services with drug sales information systems can enhance the effectiveness and efficiency of pharmaceutical services, as well as the management of drug stock in pharmacies. Through research, it is hoped to identify and analyze functional needs associated with designing and constructing e-pharmacy technology with information systems so that it can provide benefits for optimizing the use of information technology in providing users with easy access to information and enhancing the efficiency and effectiveness of technology-based services. As a consequence of the research, it is anticipated that the integration of technology in pharmacy services with a drug sales information system will yield greater community and health service benefits.